2010
DOI: 10.1177/194008291000300105
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Colombian Primates: An Analysis of Published Research

Abstract: In Colombia, there are approximately 27-31 primate species, including at least five endemic ones and a high proportion of threatened species. Differences in these primates' distribution, abundance, ecology, and charisma, among many other things, have led to large variation in the amount and nature of investigations performed on the different species. Basic information on each native primate species is necessary to build adequate conservation plans; therefore, knowledge of the quantity and type of information a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(14 citation statements)
references
References 12 publications
0
9
0
3
Order By: Relevance
“…Son escasos los estudios que se encuentran sobre la anatomía del titi gris (Stevenson et al, 2010), por lo que lograr un conocimiento de sus características morfológicas, contribuirá al significado funcional (Aversi-Ferreira et al, 2005a), como es el caso del esqueleto apendicular utilizado para la locomoción (Alexander, 1994), en el que los principales elementos para estos roles son los huesos longos (Marieb & Mallat, 1992) como el húmero (Erickson et al, 2002). Estos conocimientos, además sirven para poder explicar las diversas adaptaciones (Aversi-Ferreira et al, 2007) de los primates a su entorno, como en el caso de los primates del nuevo mundo, que son una diversa radiación de primates no humanos que ocupan amplio rango de hábitats en América, desde Méxi-co hasta Argentina (Youlatos & Meldrum, 2012) incluida Colombia.…”
Section: Introductionunclassified
“…Son escasos los estudios que se encuentran sobre la anatomía del titi gris (Stevenson et al, 2010), por lo que lograr un conocimiento de sus características morfológicas, contribuirá al significado funcional (Aversi-Ferreira et al, 2005a), como es el caso del esqueleto apendicular utilizado para la locomoción (Alexander, 1994), en el que los principales elementos para estos roles son los huesos longos (Marieb & Mallat, 1992) como el húmero (Erickson et al, 2002). Estos conocimientos, además sirven para poder explicar las diversas adaptaciones (Aversi-Ferreira et al, 2007) de los primates a su entorno, como en el caso de los primates del nuevo mundo, que son una diversa radiación de primates no humanos que ocupan amplio rango de hábitats en América, desde Méxi-co hasta Argentina (Youlatos & Meldrum, 2012) incluida Colombia.…”
Section: Introductionunclassified
“…Las investigaciones con primates en Antioquia se han concentrado en temas relacionados con ecología seguidos por estudios genéticos o moleculares, donde algunos corresponden a análisis que incluyen muestras de diferentes localidades del departamento (García-R et al, 2018). Por su parte, los estudios sobre distribución, taxonomía y sistemática son exiguos, lo que concuerda con el panorama nacional (Stevenson, Pérez-Torres, y Muñoz-Saba, 2006;Stevenson, Guzmán, y Defler, 2010;García-R et al, 2018). En este aspecto, las colecciones biológicas cumplen un papel fundamental al ser archivos de la presencia de organismos en un lugar y tiempo determinado.…”
Section: Introductionunclassified
“…White-footed tamarin (Saguinus leucopus) is a neotropical endemic and monotypic primate of Colombia (Defler, 2010) categorized by the IUCN (International Union for Conservation of Nature and Natural Resources) as an endangered species due to a significant reduction in the population, mainly due to illegal animal trade as pets (Morales-Jiménez et al, 2008). This situation makes them susceptible to arrive at the Wildlife Care and Assessment Center and zoos to be assessed by veterinarians, moreover, this species anatomical knowledge is scarce (Stevenson et al, 2010), which hinders their medical and surgical care. In a study conducted by URRAS (Unidad de Rescate y Rehabilitación de Animales Silvestres), the clinical examination revealed that a third of the greatest abnormalities were in musculoskeletal system (Varela et al, 2010).…”
Section: Introductionmentioning
confidence: 99%